Diagnosis of mucormycosis using an intercalating dye-based quantitative PCR. (21st February 2022) - Bigot, Jeanne; Godmer, Alexandre; Prudenté, Lysa; Angebault, Cécile; Brissot, Eolia; Bige, Naike; Voiriot, Guillaume; Leger, Pierre-Louis; Petit-Hoang, Camille; Atallah, Sarah; Gouache, Elodie; Senghor, Yaye; et al.
Abstract: PCR-based methods applied to various body fluids emerged in recent years as a promising approach for the diagnosis of mucormycosis. In this study, we set up and assess the value of a qPCR to detect a wide variety of Mucorales species in a single tube. A pair of degenerated primers targeting the rDNA operon was used in a qPCR utilizing an intercalating fluorescent dye. Analytical assessment, using a wide variety of both Mucorales strains (8 genera, 11 species) and non-Mucorales strains (9 genera, 14 species), showed 100% sensitivity and specificity rates with a limit of detection at 3 rDNA copy/qPCR reaction. Subsequently, 364 clinical specimens from 166 at-risk patients were prospectively tested with the assay. All the seven patients classified as proven/probable mucormycosis using the EORTC-MSG criteria had a positive qPCR as well as a patient with a proven uncharacterized invasive mold infection. In addition, three out of seven patients with possible mold invasive infections had at least one positive qPCR test. Sensitivity was calculated between 73.33 and 100% and specificity between 98.10 and 100%. The qPCR method proposed showed excellent performances and would be an important adjunctive tool for the difficult diagnosis of mucormycosis diagnosis. Lay abstract: qPCR-based diagnosis is the most reliable approach for mucormycosis. We set up a pan-Mucorales qPCR able to detect in a single reaction not less than 11 different species. Both analytical and clinical performances support its use in the clinical setting.